Protoevangelion dan Rencana Penyaliban: Analisis Teologis atas Konsistensi Rencana Keselamatan dari Allah - Yustinus Yustinus (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2026)
Contemporary theological discourse often contrasts the crucifixion of Jesus as either God's eternal plan (divine intentionality) or the result of a conspiracy between Satan and humanity (demonic causality). This study analyzes the consistency of Jesus' crucifixion as the fulfillment of God's plan of salvation rooted in the Protoevangelion (Gen 3:15) and proposes a new hermeneutical model to reconcile this dichotomy. The research employs a qualitative method with a systematic-biblical theology approach, conducted through a stage of canonical thematic analysis of key texts (from the Protoevangelion to the New Testament) and patristic sources, followed by a stage of critical hermeneutical synthesis engaging with contemporary theological thought. The study demonstrates that the crucifixion was neither Satan's plan nor merely a response to sin, but rather the consistent realization of God's eternal design. As an original contribution, this research introduces the 'Subversive Fulfillment' model, which asserts that the sovereignty of God's love actively co-opts and reverses evil plans to accomplish His salvific purpose. The findings demonstrate that this model not only resolves the theological dichotomy but also provides a foundation for a theology of the cross that affirms the sovereignty of God's love over history, suffering, and the powers of evil.AbstrakDiskursus teologi kontemporer kerap mempertentangkan penyaliban Yesus sebagai rencana kekal Allah (divine intentionality) versus hasil konspirasi Iblis dan manusia (demonic causality). Penelitian ini menganalisis konsistensi penyaliban Yesus sebagai penggenapan rencana keselamatan Allah yang berakar pada Protoevangelion (Kej 3:15) serta menawarkan model hermeneutik baru untuk merekonsiliasi dikotomi tersebut. Penelitian menggunakan metode kualitatif dengan pendekatan teologi sistematis biblika, yang dilakukan melalui tahap analisis tematik kanonis atas teks-teks kunci (dari Protoevangelion hingga Perjanjian Baru) dan sumber patristik, serta tahap sintesis hermeneutik kritis dengan pemikiran teologis kontemporer. Studi ini membuktikan bahwa penyaliban bukanlah rencana Iblis atau sekadar respons terhadap dosa, melainkan realisasi konsisten dari rancangan kekal Allah. Sebagai kontribusi orisinal, penelitian ini memperkenalkan model 'Penggenapan Subversif' yang menegaskan bahwa kedaulatan kasih Allah justru mengooptasi dan membalikkan rencana jahat untuk menggenapi maksud penyelamatan-Nya. Temuan ini membuktikan bahwa model tersebut tidak hanya memecahkan dikotomi teologis, tetapi juga menjadi landasan bagi teologi salib yang meneguhkan kedaulatan kasih Allah atas sejarah, penderitaan, dan kuasa kejahatan.